Desain Telemedicine Asam Urat Berbasis Internet of Things (IoT) - Supriyanto, Agus; Nugroho, Andi Kurniawan; Heranurweni, Sri (Elektrika, 2023)
Gout is the final metabolite of purines. Purines are part of the nucleic acids found in the nuclei of body cells. Increased gout can cause rheumatic pain in the joint area and is often associated with extreme pain for those exposed to the disease. Doctors need to monitor so that they can assist patients in monitoring and treatment. Gout detection devices are only available in hospitals, clinics, health centers, laboratories, and equipment that was previously portable but could not be controlled directly by a doctor. The purpose of this study is to help make it easier for doctors to monitor patients with gout remotely or telemedicine via the internet. The research method uses blood to determine gout levels using the Internet of Things. Data acquisition is carried out with a resistance sensor (Authocheck) which is processed by the Arduino microcontroller. The processed data is then sent to the ESP8266 web server via WiFi. The use of the Internet of Things as a data transmission method for online use does not require human-to-human interaction. The sensor resistance value in the analog range obtained is 441.03 to 782.32 with a sensor voltage of 1.91 to 3.82 volts. The measured gout level is between 4 mg/dL and 8 mg/dL. The percentage of measured data with an average accuracy of 95.74% and an average error rate of 4.26% for the seven test data. Data is displayed directly on the device's LCD screen and on a web server that sends data from the ESP8266. Keywords: gout, Internet of Things, resistance sensor (Autocheck), telemedicine, web server ABSTRAKAsam urat merupakan metabolit akhir dari purin. Purin adalah bagian dari asam nukleat yang ditemukan dalam inti sel tubuh. Asam urat yang meningkat dapat menyebabkan nyeri rematik di area persendian dan sering dikaitkan dengan rasa sakit yang luar biasa bagi yang terpapar penyakit. Dokter perlu memantau agar dapat membantu pasien dalam pemantauan dan pengobatan. Alat pendeteksi asam urat hanya terdapat di rumah sakit, klinik, puskesmas, laboratorium dan alat-alat yang sebelumnya portable namun tidak dapat dikontrol langsung oleh dokter. Tujuan dari penelitian ini membantu memudahkan dokter untuk memantau pasien dengan penyakit asam urat secara jarak jauh atau telemedicine melalui internet. Metode penelitian menggunakan darah untuk menentukan kadar asam urat menggunakan Internet of Things. Akuisisi data dilakukan dengan sensor resistansi (Authocheck) yang diproses oleh mikrokontroler Arduino. Data yang telah diproses kemudian dikirim ke web server ESP8266 melalui  WiFi. Penggunaan Internet of Things sebagai metode transmisi data untuk penggunaan secara online tidak memerlukan interaksi manusia ke  manusia. Nilai  resistansi sensor pada rentang analog yang diperoleh adalah 441,03 hingga 782,32 dengan tegangan sensor 1,91 hingga 3,82 volt. Kadar asam urat yang diukur adalah antara 4 mg/dL dan 8 mg/dL. Persentase data terukur dengan akurasi rata-rata 95,74% dan rata-rata tingkat kesalahan  4,26% untuk tujuh data uji. Data ditampilkan langsung di layar LCD perangkat dan di web server yang mengirimkan data dari ESP8266.